USE OF ROCK SLURRY IN THE SYNTHESIS OF GEOPOLYMERS: ENVIRONMENTAL AND TECHNOLOGICAL ASPECTS - Скиба, Галина (SWorldJournal, 2025)
Stone slurry, as a secondary product of the stone processing industry, is considered a promising raw material for geopolymer materials. The study of its chemical composition showed a high content of SiO₂ relative to Al₂O₃, which meets the requirements for